The Association of Pre-existing Diagnoses of Alzheimer’s Disease and Parkinson’s Disease and Coronavirus Disease 2019 Infection, Severity and Mortality: Results From the Korean National Health Insurance Database - Kim, Ji Hee; Chang, In Bok; Kim, Yoo Hwan; Min, Chan Yang; Yoo, Dae Myoung; Choi, Hyo Geun (Frontiers in Aging Neuroscience, 2022)
Objectives: Despite the numerous studies on coronavirus disease 2019 (COVID-19), data regarding the impact of preexisting diagnoses of Alzheimer’s disease (AD) and Parkinson’s disease (PD) on the susceptibility to and outcome of COVID-19 are limited. We aimed to determine whether patients with AD/PD had a higher likelihood of contracting COVID-19 and experiencing worse outcomes. Methods: Data from patients with confirmed diagnoses of COVID-19 (n = 8,070) from January to June 2020 and control participants (n = 121,050) who were randomly selected to match the patients on the basis of age and sex were extracted from the Korean National Health Insurance Database. Preexisting diagnoses of AD and PD were identified based on medical claim codes. The associations of preexisting AD or PD with contracting COVID-19, developing severe COVID-19 and dying due to COVID-19 were examined using a logistic regression model. The participants’ age, sex, income, comorbidity score, and history of hypertension/diabetes were assessed as covariates. Results: COVID-19 cases were more likely to have a preexisting AD diagnosis (adjusted odds ratio [aOR]=2.11, 95% confidence interval [CI]=1.79-2.50, P value <0.001) than controls. COVID-19 cases were more likely to have a preexisting PD diagnosis than controls, although this estimate did not quite reach statistical significance (aOR=1.41, 95% CI=1.00-2.00, P value=0.054). Preexisting AD was related to severe disease and mortality from COVID-19 (aOR=2.21, 95% CI=1.64-2.98; aOR=2.21, 95% CI=1.00-2.00). Preexisting PD was not associated with mortality (aOR=1.54, 95% CI=0.75-3.16) but was associated with severe disease (aOR=2.89, 95% CI=1.56-5.35). Conclusion: We found that COVID-19 infection was significantly associated with a preexisting diagnosis of AD but not with a preexisting diagnosis of PD. Patients with preexisting AD had higher odds of developing severe COVID-19 and dying. Preexisting PD was only associated with a higher odds of developing severe COVID-19.